Peran Social Media Fitness Influencers (SMIs) terhadap Keputusan Pembelian Produk Kebugaran - Robi Putra Sujudi; Raden Roro Ratna Roostika (Penerbit Goodwood, 2025)
Purpose: This study aimed to analyze the effect of physical attractiveness and social attractiveness on the purchase intention of fitness products, with trustworthiness and perceived expertise as intervening variables. Methodology/Approach: This study uses a quantitative approach. Data collection involved distributing online questionnaires to 200 respondents using Google Forms. The sampling technique used was a non-probability sampling technique using the purposive sampling method, which was then processed using Structural Equation Modeling (SEM) using the PLS program. Results: This study found that physical attractiveness had a positive and significant effect on trustworthiness. Physical attractiveness has a positive and significant effect on perceived expertise. Social attractiveness had a positive and significant effect on trustworthiness. Social attractiveness has a positive and significant effect on perceived expertise. Trustworthiness has a positive and significant effect on purchase intention. Perceived expertise has a positive and significant effect on purchase intention. Conclusions: Physical attractiveness and social attractiveness both have a significant positive influence on trustworthiness and perceived expertise, which in turn significantly enhance purchase intention for fitness products. Trust and perceived expertise act as essential mediating variables that strengthen the relationship between attractiveness and consumer purchase intention. Fitness products promoted by individuals who are physically and socially appealing, trustworthy, and perceived as experts are more likely to attract consumer interest. Limitations: The number of respondents and the variables used were limited to physical and social attractiveness, with trustworthiness and perceived expertise as intervening variables. Thus, other possible variables could influence the purchase intention of fitness products. Contribution: This study contributes to the determination of corporate policies to increase purchase intention using physical attractiveness, social attractiveness, trustworthiness, and perceived expertise as intervening variables.